The Role of the Substitute Registrar in Handling Appeal Case Files in Religiou’s Court Makassar - Lira, Adnan; Asriati (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
After the birth of Law no. 7 of 1989 concerning Religious Courts, there is hope that an independent Religious Court and Religious High Court will be realized. This type of research is empirical legal research, namely legal research that focuses on legal realities in society or is low in action. The location of this research was the Makassar High Religious Court. The type of data in this research is primary data, namely judges and clerks at the Makassar Religious High Court through questionnaires and direct interviews. As well as secondary data are official documents, scientific journals, legislation and official data which are products of the Makassar High Religious Court. Data analysis in this research uses qualitative and quantitative data analysis techniques. Qualitative analysis is a means of analyzing data that cannot be quantified, namely that which is still interpretative. The results of the research show that the role of the Substitute Registrar in handling appeal case files at the Makassar Religious High Court has been carried out well, but in some cases it is less effective. This can be seen from the low level of understanding of administrators' responsibilities in carrying out and completing appeal case files and submitting a copy of the decision to the court of first instance. Factors that influence the implementation of the duties and functions of the Substitute Registrar are matters of legal structure, legal culture, and facilities and infrastructure.